Digitalization of Civil Servants’ Performance in The Tomohon - Minahasa Branch Regional Education Services - Tairas, Selvian Lidia; Mandagi, Marthinus; Tarore, Steven (Technium Social Sciences Journal, 2024)
The E-Performance application for Civil Servants is a system used to monitor, evaluate and manage the performance of employees in a government agency. This application is usually developed as part of modernization and bureaucratic reform efforts to increase efficiency, transparency and accountability in the implementation of government tasks. This research aims to 1) To determine and analyze the use of the E-Performance application for civil servants in the Tomohon-Minahasa Branch Regional Education Office; 2) To find out and analyze what are the factors inhibiting the use of the E-Performance application for civil servants with different numbers of employee allowance recipients at the Tomohon-Minahasa Branch Regional Education Office. The type of research used is qualitative research. The data collection techniques used are observation, interviews and documentation. The research results show that in using e-Performance , all work units in the education department collaborate well and share information with each other. The attendance mechanism in the e-Performance application requires State Civil Apparatus (ASN) to be present on time and their presence cannot be delegated. The implementation of the use of e-Performance encourages ASN "forcibly" to be disciplined in terms of attendance. The reward and punishment system after using e-Performance is very transparent. Resources to support application use are available. Those who experience problems with the application device are caused by their own negligence, such as not understanding the features in the application and not personally owning an Android cellphone. Collaboration between units or sections within the relevant education service regarding the use of the e-Performance application is very good.